PENGARUH PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU POSTPARTUM - Zara Faiza; Dewi Rachmawati; Mujito Mujito (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2023)
Introduction: Inadequate expenditure of breast milk on the first day after birth is an obstacle in early breastfeeding in infants. The mother's difficulty in breastfeeding because the milk does not come out causes the milk to dam up and the baby often cries. One of the efforts made to stimulate breast milk production is to massage the spine, which is called oxytocin massage. The purpose of this study was to determine the effect of oxytocin massage on postpartum mothers by identifying milk production before, after, and the effect of oxytocin massage. Methods: The literature review design is a traditional review, the literature search method uses the PEOS framework which consists of P (Population): postpartum mothers, E (Exposure): oxytocin massage, O (Outcome): increase milk production in postpartum mothers, S (Study Design): Pre-experimental one group pretest posttest, Quasi experimental the static group comparison, Experimental posttest with control group, Quasi experiment posttest only design with control group. Study selection used the keywords “milk production, postpartum mothers, oxytocin massage” on the Google Scholar database as a whole found 2,780 articles then were selected based on the year of publication of the articles (2015-2021) to 2,500 articles, topic suitability and title to 71 articles, full text downloadable into 23 articles and finally based on the study design, 7 articles were obtained which carried out a literature review. Results: Based on the 7 articles that have been analyzed, it shows that there is a significant effect of oxytocin massage on milk production with a p-value <0.05 because oxytocin massage can increase feelings of comfort and relaxation so that the body can easily release the hormone oxytocin which has an impact on expenditure and increased production of ASI. Conclusion: For this reason, it is necessary to have the role of health workers as educators to provide health education about the importance of doing oxytocin massage in postpartum mothers.